2011
DOI: 10.1093/jnci/djq569
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lysyl Oxidase in SRC-Dependent Proliferation and Metastasis of Colorectal Cancer

Abstract: LOX showed an important role in CRC cell proliferation and metastasis and was dependent on the activation of SRC. These results have the potential to identify patients with high SRC activity, who may benefit from dasatinib treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
193
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(211 citation statements)
references
References 53 publications
13
193
1
1
Order By: Relevance
“…18 We mainly used this pair of cell lines in this study, because they had the same genetic background with different metastatic potential. 19 To evaluate their metastatic activities in vivo, we performed the orthotopic transplantation model of CRC metastasis in mice 6,17,20 with the use of GFP marker. After injecting the cells into the rectal smooth muscle layer of nude mice, we macroscopically examined metastatic foci using GFP fluorescence.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…18 We mainly used this pair of cell lines in this study, because they had the same genetic background with different metastatic potential. 19 To evaluate their metastatic activities in vivo, we performed the orthotopic transplantation model of CRC metastasis in mice 6,17,20 with the use of GFP marker. After injecting the cells into the rectal smooth muscle layer of nude mice, we macroscopically examined metastatic foci using GFP fluorescence.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…Because the leading cause of deaths of patients with colon cancer is the metastatic dissemination and in particular the liver colonization, it is imperative to assess the therapeutic benefits of a new compound on experimental models of metastatic disease. The experiments we performed in a well-established model of colon dissemination disease, by intrasplenic injection of tumor cells (42,43), demonstrated that EMICORON treatment is able to inhibit the spreading of metastasis to both gastrointestinal organs and liver. The most recent class of preclinical models is PDXs, where tumor fragments from patients are directly implanted in immunodeficient mice and then passed directly from mouse to mouse in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…LOX is one of the critical HIF-1 targets mediating tumor progression and catalyzes the cross-linking of collagens and elastin in the extracellular matrix, thereby regulating tissue tensile strength (Erler & Giaccia, 2006). Paradoxically, LOX has been reported to be both up-regulated and down-regulated in cancer cells, especially in colorectal cancer (Baker, 2011;Pez, 2011). Mechanistic investigations revealed that LOX activates the PI3K-Akt signaling pathway, thereby upregulating HIF-1 protein synthesis in a manner requiring LOX-mediated hydrogen peroxide production.…”
Section: Discussionmentioning
confidence: 99%